2004
DOI: 10.1002/nag.390
|View full text |Cite
|
Sign up to set email alerts
|

A continuum‐discrete hydromechanical analysis of granular deposit liquefaction

Abstract: SUMMARYA coupled continuum-discrete hydromechanical model was employed to analyse the liquefaction of a saturated loose deposit of cohesionless particles when subjected to a dynamic base excitation. The pore fluid flow was idealized using averaged Navier-Stokes equations and the discrete element method was employed to model the solid phase particles. A well established semi-empirical relationship was utilized to quantify the fluid-particle interactions. The conducted simulations revealed a number of salient mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 29 publications
1
48
0
2
Order By: Relevance
“…The hydrostatic force acting on a single particle, i, accounts for the influence of fluid pressure gradient around the particle (i.e. buoyancy) (Chen et al 2011;Kafui et al 2011;Zeghal and El Shamy 2004), as shown in Eq. (3).…”
Section: Fluid-particle Interactionmentioning
confidence: 99%
“…The hydrostatic force acting on a single particle, i, accounts for the influence of fluid pressure gradient around the particle (i.e. buoyancy) (Chen et al 2011;Kafui et al 2011;Zeghal and El Shamy 2004), as shown in Eq. (3).…”
Section: Fluid-particle Interactionmentioning
confidence: 99%
“…The hydrostatic force accounts for the fluid pressure gradient around an individual particle (i.e. buoyancy) [27,40,41], expressed as:…”
Section: Fluid-particle Interactionmentioning
confidence: 99%
“…The amount of this force can be estimated by using semi-empirical equations. The Ergun's equation is one of the most well-known equations in this field [2,5] which can be used to estimate the drag force on particles from laminar to turbulent flow. Thus, the total force acting on each particle in a fluid cell is:…”
Section: Coupled Fluid-dem Algorithmmentioning
confidence: 99%
“…In their proposed method a background mesh is considered for the fluid phase and continuity and momentum (Navier-Stokes) equations were solved to calculate the averaged velocity and pressure of the fluid on those fixed coarse grids; the fluid equations can take into account the solid part as their porosity. Shimizu [4] added thermal equations to this scheme, and Zeghal and Shamy [5] implemented this approach to look at pore pressure generation in granular deposits under shaking loading. They observed the generated pore pressure and velocity in dynamic conditions in sandy soil and pointed out that fluid velocity in their examples does not exceed laminar regime.…”
Section: Introductionmentioning
confidence: 99%